Systematic in vitro biocompatibility studies of multimodal cellulose nanocrystal and lignin nanoparticles - Imlimthan, Surachet; Correia, Alexandra; Figueiredo, Patrícia; Lintinen, Kalle; Balasubramanian, Vimalkumar; Airaksinen, Anu J.; Kostiainen, Mauri A.; Santos, Hélder A.; Sarparanta, Mirkka (Journal of biomedical materials research. Part A, 2020)
Natural biopolymer nanoparticles (NPs), including nanocrystalline cellulose (CNC) and lignin, have shown potential as scaffolds for targeted drug delivery systems due to their wide availability, cost‐efficient preparation, and anticipated biocompatibility. As both CNC and lignin can potentially cause complications in cell viability assays because of their ability to scatter the emitted light and absorb the assay reagents, we investigated the response of bioluminescent (CellTiter‐Glo®), colorimetric (MTT® and AlamarBlue®), and fluorometric (LIVE/DEAD®) assays for the determination of the biocompatibility of the multimodal CNC and lignin constructs in murine RAW 264.7 macrophages and 4T1 breast adenocarcinoma cell lines. Here, we have developed multimodal CNC and lignin NPs harboring the radiometal chelator 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid and the fluorescent dye cyanine 5 for the investigation of nanomaterial biodistribution in vivo with nuclear and optical imaging, which were then used as the model CNC and lignin nanosystems in the cell viability assay comparison. CellTiter‐Glo® based on the detection of ATP‐dependent luminescence in viable cells revealed to be the best assay for both nanoconstructs for its robust linear response to increasing NP concentration and lack of interference from either of the NP types. Both multimodal CNC and lignin NPs displayed low cytotoxicity and favorable interactions with the cell lines, suggesting that they are good candidates for nanosystem development for targeted drug delivery in breast cancer and for theranostic applications. Our results provide useful guidance for cell viability assay compatibility for CNC and lignin NPs and facilitate the future translation of the materials for in vivo applications.